A Novel Web Usage Mining Technique Analyzing Users Behaviour Using Dynamic Web log - Sharma, Priyanka; Gupta, RK (International Journal of Computer Sciences and Engineering, 2025)
WWW-world wide web is one of the most required resource for getting information and knowledge. Several organizations rely on websites to get new customers and to hold the existing one. The customer’s surfing pattern can be obtained by web log record. This is a kind of work in the arena of web usage mining. The paper proposed the novel methodology by mining the usage of patters from web log records of real time. Ontology of the web content including user profiles and external data can be developed by Web usage mining. In this paper a method is proposed for discovering and tracking the growing user profiles along with domain specific information facets. To judge the quality of the obtained profiles after mining an objective validation plan is also used. Through this research organizations can take better decision by getting better recommendation